2021
DOI: 10.1007/s11250-021-02777-1
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid profile in the breast and thigh muscles of the slow- and fast-growing birds under the same management system

Abstract: The aim of the study was to assess the effect of feeding the same diet to different breeds of chickens and at different ages on fatty acid (FA) composition of the breast and thigh muscles. A total of 150 chickens comprising 50 each of red jungle fowl (RJ) and village chicken (VC), the slow-growing birds, and the commercial broiler (CB), fast-growing birds, were used for this study. Ten chickens from each breed were serially euthanized at days 1, 10, 20, 56, and 120 post hatch, and pectoralis major and bicep fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 24 publications
4
10
0
Order By: Relevance
“…Also, the contents of the essential fatty acids in breast meat were higher than those in the thigh meat. These results are in agreement with those of Mahiza et al, which reported that the compositions of MUFA were lower and the compositions of PUFA were higher in slow-growing birds than in fast-growing birds [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…Also, the contents of the essential fatty acids in breast meat were higher than those in the thigh meat. These results are in agreement with those of Mahiza et al, which reported that the compositions of MUFA were lower and the compositions of PUFA were higher in slow-growing birds than in fast-growing birds [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, we conducted an in-depth investigation of the effect of FAs on the deposition of TG, PLIP, and IMF in the selected line and control line. The results on the FA composition revealed that the long chain FAs (LCFAs), including C16:0, C18:0, C18:1n9c, C18:2n6c and C20:4n6, were more prevalent prevailing with a proportion exceeding 10% in chicken meat as previously reported [ 34 ], which can explain the 95.34% phenotypic contribution determined by PCA analysis in this study. Further, by separately isolating TG and PLIP using each eight individuals in the groups with the high- or low-IMF contents, we found that the FA composition of IMF is mainly determined by TG, not by PLIP.…”
Section: Discussionsupporting
confidence: 85%
“…It was known that LCFAs (such as C16:0, C18:0, C18:1n9c, C18:2n6c, et al) were the main FA composition of fat [ 34 ]. In this study, the proportions of LCFAs (C14:0, C16:1, C18:1n9c, C18:3n3, et al) in the selected line than those of the control line were increased, accompanied with the high positive correlations of TG and IMF.…”
Section: Discussionmentioning
confidence: 99%
“…In the slow-growing chicken breeds, chickens have more muscle and subcutaneous fat, and the fat distribution is more even [3]. The total fat content in fast-growing chickens is greaterhigher than that in slow-growing chickens, and the fat is mainly distributed in the abdomen and on the visceral surfaces, the compositions of monounsaturated fatty acids A c c e p t e d A r t i c l e (MUFA) were lower and the compositions of polyunsaturated fatty acids (PUFA) were higher in slow-growing than fast-growing chickens [4]. The low intramuscular fat usually results in a poor meat quality [5].…”
Section: Introductionmentioning
confidence: 99%